DOP060 Human amnion epithelial cells and their conditioned media reduces intestinal inflammation and fibrosis in a murine model of chronic colitis. (16th January 2018) - Kuk, N; Correia, J; Alhomrani, M; Lim, R; Sievert, W; Hodge, A; Moore, G
Abstract: Background: Inflammatory bowel disease (IBD) requires lifelong therapy to control symptoms. Despite therapeutic advances, some patients experience debilitating side effects or are refractory to conventional treatment. Current treatments do not reduce or reverse established intestinal fibrosis. Isolated from placentas, human amnion epithelial cells (hAECs) are pluripotent stem cells that possess anti-inflammatory and anti-fibrotic properties. With no tumourogenicity and an excellent safety profile, hAECs are a promising novel therapy for IBD. We examined the efficacy of hAECs and its conditioned media (CM) in a dextran sulphate sodium (DSS) induced murine model of chronic colitis. Methods: C57BL/6J mice received a cycle of 2% DSS (w/v) in normal water for one week then normal water for two weeks. This three-week cycle was repeated twice until cull at week 10. Beginning at week 6, the Chronic DSS group administered hAECs (Chr-hAEC, n = 14) received weekly tail vein injections of 2million hAECs; the Chronic DSS group administered CM (Chr-CM, n = 15) group received 250uL CM three times weekly. Normal mice ( n = 7) and DSS control mice (Chr-DSS, n = 13) received no therapy. Mice were monitored daily. Colitis severity was scored using H&E stained colon sections. IL-1β, TNF-α, IL-6, TGF-β, IFN-γ, IL-10 were measured by ELISA. Fibrosis extent was measured via computer-assisted morphometry of picro-sirius stained colon sections. Fibroblasts and macrophages were identified by immunohistochemistry (α-SMA, F4/80). Results: Untreated control DSS mice gained significantly less body weight (4.2%) compared with hAEC (10%, p < 0.05) and CM (12.5%, p < 0.001) treated mice. hAECs and CM prevented colon shortening (6.75 cm, p < 0.001 and 7.3 cm, p < 0.0001 respectively) compared with controls (5.9cm). Splenomegaly was greater in Chr-DSS (212 mg) than hAEC (160 mg, p < 0.05) and CM (134 mg, p < 0.001) treated mice. Compared with controls, hAEC ( p < 0.0001) and CM treatment ( p < 0.01) significantly lowered histological severity. Likewise, IL-1β, TNF-α, IL-6, IFN-γ were significantly higher in untreated DSS mice. hAEC therapy up-regulated IL-10 but not TGF-β. hAECs and CM significantly ameliorated fibrosis by 44% ( p < 0.0001) and 37% ( p < 0.0001) respectively and reduced myofibroblasts and macrophage numbers. There were no significant differences between Chr-hAEC and Chr-CM mice. Conclusions: hAECs and its CM markedly reduce disease severity in DSS induced chronic colitis. The protective effects were associated with reductions in pro-inflammatory and increases in anti-inflammatory cytokines. Fibrosis was resolved through reductions in macrophage and myofibroblasts numbers. The positive effects of hAECs and CM in IBD are promising although further research into their mechanism of actions is warranted.